2012
DOI: 10.1016/j.immuni.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4-Driven Neutrophil Recruitment to the Skin Is Essential for Allergic Skin Inflammation

Abstract: Summary Scratching triggers skin flares in atopic dermatitis (AD). We demonstrate that scratching of human skin, and tape stripping of mouse skin, causes neutrophil influx. This influx in mice was largely dependent on the generation of leukotriene B4 (LTB4) by neutrophils and their expression of the LTB4 receptor BLT1. Allergic skin inflammation in response to epicutaneous (EC) application of ovalbumin to tape-stripped skin was severely impaired in Ltb4r1−/− mice, and required expression of BLT1 on both T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
136
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(151 citation statements)
references
References 37 publications
9
136
1
Order By: Relevance
“…20, 21 Neutrophil recruitment is a hall mark of innate immune responses, 22 and innate recruitment of neutrophil to the skin through leukotriene B4 (LTB4) is critical for induction of subsequent allergic skin inflammation. 22, 23 We recently reported that RWPE challenge induces CXCR2 and TLR4-dependent innate recruitment of activated neutrophils to the airways, and these recruited neutrophil are critical for induction of allergic sensitization and allergic airway inflammation. 6 In the present study, we extend our earlier observations by demonstrating a broad role of MD2 in induction of innate and allergic airway inflammation and allergic sensitization by CDE, RWPE and extracts of pollens from grasses, weeds and trees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20, 21 Neutrophil recruitment is a hall mark of innate immune responses, 22 and innate recruitment of neutrophil to the skin through leukotriene B4 (LTB4) is critical for induction of subsequent allergic skin inflammation. 22, 23 We recently reported that RWPE challenge induces CXCR2 and TLR4-dependent innate recruitment of activated neutrophils to the airways, and these recruited neutrophil are critical for induction of allergic sensitization and allergic airway inflammation. 6 In the present study, we extend our earlier observations by demonstrating a broad role of MD2 in induction of innate and allergic airway inflammation and allergic sensitization by CDE, RWPE and extracts of pollens from grasses, weeds and trees.…”
Section: Discussionmentioning
confidence: 99%
“…29 This MD2/TLR4-induced innate neutrophil recruitment facilitates allergic sensitization and allergic airway inflammation. 6, 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allergic skin inflammation in response to the epicutaneous application of ovalbumin to tapestripped skin is severely impaired in BLT 1 -deficient mice. 117 In mice, the itch-eliciting activity of sphingosylphosphorylcholine is mediated by the direct action of LTB 4 produced by keratinocytes. 118 NC/Nga mice with AD-like skin lesions show a significant increase in LTB 4 levels in the lesional skin; however, topical application of the BLT 1 antagonist, ONO-4057, inhibits spontaneous itch-related behavior.…”
Section: Ltb 4 and Atopic Dermatitismentioning
confidence: 99%
“…The expression of eosinophilactive chemokines in the skin is primarily regulated by the T H 2 cytokines IL-4 and IL-13, which are abundantly expressed in the skin after BLT1-mediated T H 2 cell recruitment (34). Additionally, a CCR8+ T H 2 cell subtype enriched in IL-5 is recruited to the skin (48,49).…”
Section: Expression Of Leukotrienes In Inflammatory Skin Diseasesmentioning
confidence: 99%